Volatilomik Daging Babi dengan Berbagai Metode Pengolahan Berdasarkan SPME-GC-MS: Volatilomics Of Pork With Various Processing Methods Based On SPME-GC-MS - Lia Amalia; Irdawati Baswir; Intan Kusumaningrum; Aji Jumiono; Mardiah Mardiah; Erna Puspasari (Universitas Djuanda, 2026)
Meat adulteration is a significant issue in the food supply chain due to its relevance to halal compliance. Pork is often used as a substitute for beef because of its similar physical characteristics and lower price, while visual identification becomes increasingly difficult after processing. This study aimed to analyze the volatile compound profile of pork processed by boiling, frying, and roasting using the Solid Phase Microextraction–Gas Chromatography–Mass Spectrometry (SPME–GC-MS) technique. Each processing treatment was conducted with five replications. The results showed that boiled and fried pork each contained 169 volatile compounds, while roasted pork contained 176 volatile compounds. The dominant compounds mainly belonged to the aldehyde group, including hexanal, nonanal, octanal, and heptanal, as well as long-chain aldehydes such as pentadecanal and heptadecanal, which are associated with lipid oxidation during processing. In addition, alcohols such as 1-hexanol and 1-octen-3-ol, as well as heterocyclic compounds such as 2-pentylfuran and 2-pentylthiophene, also contributed to the resulting volatile profile. These findings indicate that the volatile profile obtained through a volatilomic approach has the potential to serve as a basis for the identification and authentication of pork in processed food products.